Discovery of steroidal alkaloid glycosides from the bulbs of Fritillaria unibracteata with anti-inflammatory activities using an in vivo zebrafish model. (December 2022) - Wang, Shu-Hui; Wang, Yu-Qi; Lv, Tian; Ai, Xiao-Ni; Kathy Tse, Wai-Gaun; Liang, Hong; Yang, Tie-Chui; Zhang, Qing-Ying; Tu, Peng-Fei
Abstract: Nine undescribed steroidal alkaloid glycosides, unibrasolanosides A-F, unibraverazosides A-B, and unibratomatoside A, were isolated from the bulbs of Fritillaria unibracteata P. K. Hsiao & K. C. Hsia (Liliaceae). Their structures were elucidated by HRESIMS and 1D and 2D NMR data analyses as well as chemical methods and single-crystal X-ray diffraction analyses. Further investigation revealed that eight steroidal alkaloid glycosides displayed moderate anti-inflammatory activity in vivo in a CuSO4 -induced transgenic zebrafish model. Graphical abstract: Image 1 Highlights: Nine undescribed steroidal alkaloid glycosides were isolated from the bulbs of Fritillaria unibracteata. The solanidine, verazine, and tomatillidine type steroidal alkaloid were isolated from F. unibracteata for the first time. Eight steroidal alkaloid glycosides displayed anti-inflammatory activity in a CuSO4 -induced transgenic zebrafish model.